Evaluating Halal Certification Assessment on Madurese Tourism Destination - Shofiyun Nahidloh; Lailatul Qadariyah; Firman Setiawan; Trischa Relanda Putra; Tri Pujiati (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2025)
This study assesses halal certification and implementation of halal tourism practices in selected tourist destinations on Madura Island, Indonesia, namely Pasarean Syaikhona Kholil, Asta Tinggi, Lon Malang Beach and Bukit Tinggi Daramista. Using a qualitative case study design, data were gathered through in-depth interviews, focus group discussions, participant observation and document analysis and were evaluated using halal tourism indicators derived from Islamic jurisprudence, national halal certification regulations, and ulama-based guidelines. The findings indicate that although these destinations do not formally designate themselves as halal tourism sites, they have substantially integrated halal tourism principles into their management and services as reflected in the availability of halal food and beverages, adequate worship facilities, cleanliness and sanitation, the absence of non-halal activities and strong managerial commitment to Islamic values supported by religious authorities. From the perspective of Islamic law particularly through the framework of maqÄá¹£id asy-syarÄ«â€™ah, fiqh muâ€™Ämalah and fiqh al-Ê¿ÄdÄt, these practices demonstrate substantive compliance with SyarÄ«â€™ah objectives in safeguarding religious observance, public welfare, moral integrity and economic justice. Nevertheless, the persistence of partial halal certification, limited disability-friendly infrastructure and fragmented Islamic information systems underscores the need for gradual institutional strengthening, improved regulatory coordination and closer collaboration with halal certification authorities to enhance the sustainability and legal certainty of halal tourism development in Madura.